Integritas Guru Pak Dalam Membentuk Karakter Rohani Peserta Didik - Fitri Anggela; Nicodemus Sabudin (Jurnal Pendidikan Agama dan Teologi, 2023)
In writing this article, we discuss the integrity of PAK teachers in forming the spiritual character of students. Because nowadays, there are still some teachers who have not been able to show a Christlike attitude to life, so they are not a good role model for students. In fact, the integrity of an PAK teacher directs the behavior of students so that they are successful in following lessons in a certain knowledge environment. In fact, the integrity of an PAK teacher directs the behavior of students so that they are successful in following lessons in a certain knowledge environment. The results of the research show that there are several things that educators need to pay attention to in forming a child's spiritual character, namely: First, maintaining the sanctity of his life as God's partner in educating. Second, directing his students to become students like him and realizing that he is a servant of God whose job is to teach God's word to all nations. Third, Christian religion teachers must prepare lessons as well as possible.Fourth, Christian religious teachers must be role models and have integrity and be friendly to students in the context of forming the spiritual character of students.  This study used the cauldron method qualitative with the library data used are the Bible, journals, articles and theological books that support the topic of discussion.